PENGARUH KINERJA LIMA PILAR IRIGASI TERHADAP INDEK KESIAPAN MODERNISASI IRIGASI (IKMI) PADA DAERAH IRIGASI SEUSEUPAN DI KABUPATEN CIREBON - Sopiyan, Cecep (Jurnal Media Teknologi, 2026)
Seuseupan Irrigation Area Cirebon Regency is still a conventional Irrigation Area,where there are influences on the performance of five irrigation pillars, among others theinfluence of irrigation water supply, tyhe influence of irrigation facilities and infrastructureimproments, the effect of improving irrigation management, the effect of improving irrigationmanagement systems, the influence of strengthening irrigation management institutions, andthe influence of resource emprowerment hhuman power ot irrigation managers to increasefrom conventional irrigation areas to modern irrigation areas.Towards modernization must go through several steps that must be carried out,among others by compiling an index or irrigation modernization readiness as in Indonesian isIndeks Kesiapan Modernisasi Irigasi or we call it IKMI, and researchers analyzing using pathanalysis to prove that there are influences or not the performance of five pillars on IKMI.The results of the preparation of IKMI based on primary data (Quantity) in theSeuseupan Irrigation District of Cirebon Regency are as follows : Water Source (X1) :14.15%, Infrastructure (X2) : 19,50%, Management (X3) : 12.18%, Institution (X4) : 16.29%,dan SDM (X5) : 14.38% So the value of IKMI (Y) 76.49% (predicate sufficient, modernizationis postponed, improvements are made according to the results of IKMI 1-2 years). Inconclusion, the Seuseupan Irrigation Area of Cirebon Regency is not yet ready to be madeinto a modern irrigation area. The order of influence is greater than the other variabels on thevalue of IKMI (Y).Level that have t test results between the five independent variables on the dependentvariable are (1) Infrastructure (X2) has a t count of 4997,820, (2) Human Resources (X5) tcount results of 4716,245, (3) Managing Institution (X4) results of t count of 4288,325, (4)Sourcea of water (X1) has a results of t count of 3889,125 and (5) Management (X3) of tcount of 2828,378.